Remodelación de una vivienda unifamiliar a un “Coffee Shop-Barista Lab” - Lanas Palacios, Stefanie (2015)
The present project of titulación consists in a proposal for the readecuación of a house unifamiliar of two plants in a Coffee Shop - Barista Lab, like a new architectonic typology for the country. Same that is located at the corner of Valladolid and Vizcaya streets, in front of the Ocho y Medio cinema, in the Floresta sector. The project consists of the change of land use of a heritage single-family home, to a Coffee Shop - Barista Lab, that is, a type of cafeteria with semi-independent environments, shelves with books and magazines, exhibition spaces for coffee processes, a space for roasting it as an integrated area with the rest of the cafeteria and a Barista School. It has managed to develop an interior architectural proposal that achieves an aesthetic and functional balance, in order to achieve an ideal readjustment to offer a new architectural typology to the city of Quito and that this can increase the coffee culture and promote the tourist growth of the city. La Floresta neighborhood, without affecting the original typology of the building and preserving its heritage facades.